2022
DOI: 10.1049/itr2.12191
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive personalized routing for vulnerable road users

Abstract: This research presents an adaptive and personalized routing model that enables individuals with mobility impairments to save their route preferences to a mobility assistant platform. The proactive approach based on anticipated user need accommodates vulnerable road users' personalized optimum dynamic routing rather than a reactive approach passively awaiting input. Most currently available trip planners target the general public's use of simpler route options prioritized based on static road characteristics. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…This difficulty level merges the psychological burden experienced by wheelchair users, computed via the Analytic Hierarchy Process using user-input data, with the physical burden, based on the data collected for the study, to emulate user route selection within the system. Darko et al (2022) suggested a route search methodology adapted to each user's psychological and physiological states, specifically tailored for individuals with disabilities. The problem is modeled by considering personalized preferences, which change over time, sidewalk segment traversability, and the interaction between sidewalk factors and weather conditions that contribute to path selection.…”
Section: Related Workmentioning
confidence: 99%
“…This difficulty level merges the psychological burden experienced by wheelchair users, computed via the Analytic Hierarchy Process using user-input data, with the physical burden, based on the data collected for the study, to emulate user route selection within the system. Darko et al (2022) suggested a route search methodology adapted to each user's psychological and physiological states, specifically tailored for individuals with disabilities. The problem is modeled by considering personalized preferences, which change over time, sidewalk segment traversability, and the interaction between sidewalk factors and weather conditions that contribute to path selection.…”
Section: Related Workmentioning
confidence: 99%
“…The following is a summary of representative studies and their differences from this study. Darko et al proposed a route search method adapted to each user's physical condition for people with disabilities (Darko, 2022). A model based on the hierarchical analysis method is created for each user's preference for sidewalks, depending on the time of day, sidewalk conditions, weather, etc.…”
Section: Related Workmentioning
confidence: 99%
“…Public transportation provided in cities including the first and last mile travel is a key part of urban development, which contributes to sustainable cities and communities. The mobility system in most cities has immense importance for urban dwellers, particularly for vulnerable groups, such as low-income groups, pregnant women, children, physically challenged persons, and senior citizens who have less access to a private vehicle and rely on public transportation [1,2]. Mobility is essential for accessing physical, social, and cultural activities, connecting neighborhood facilities, and engaging in social participation.…”
Section: Introductionmentioning
confidence: 99%
“…Mobility also supports healthy aging and quality of life as it promotes the physical movement of humans [3]. But without mobility equality and equitability, public transportation services provided to vulnerable road users in society such as senior citizens may be inhibited from participating in social activities [2]. Most senior citizens rely on driving to accomplish their mobility needs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation